A STUDY OF EFFECTIVE ENGLISH LANGUAGE TEACHERS AT SENIOR HIGH SCHOOL LEVEL IN MAKASSAR - Asriati, Asriati; Atmowardoyo, Haryanto; Sukardi, Weda (ELT WORLDWIDE, 2015)
ABSTRACT An effective English language teacher has different characteristics from an ordinary one. This research was conducted to reveal the characteristics of effective English language teachers in Makassar and the backgrounds of effective English language teachers that contribute to develop their abilities in teaching. This research applied a qualitative research method using case study approach. The findings of this research show that the characteristics of effective English language teachers in Makassar are divided into several categories; professional competence, pedagogical competence, social competence, personal qualities, and intra and intercultural awareness. Effective English language teachers emphasized their characteristics mostly on professional and pedagogical competence while the students categorized their teachers based on their personal qualities. In terms of personal background, there are several characteristics that could be concluded, they were inspired by their teachers that make them interested in English and become English teachers, they have positive attitudes toward English since they were students, and the second and the third research subject come from teachersâ family while the first research subject does not come from teachersâ family, but they all admitted that their families have important roles to their career as teachers. Keywords: Effective Teachers, Teacher Characteristics, Teachersâ Personal Background